Value conflicts experienced by muslim counsellors in counselling muslim effeminate clients - Syarifah Rohaniah binti Syed Mahmood (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The provisions of the counselling code of ethics and the guidelines for dealing with lesbian, gay, bisexual, and transgender (LGBT) clients are seen to be contrary to the religious beliefs and practices of counsellors in Muslim societies. The difference between the provisions and expectations of the counselling profession and religious values are bound to create value conflicts among Muslim professional counsellors. The purpose of this grounded theory study is to develop a theory that explains how Muslim counsellors experience value conflicts in counselling Muslim effeminate clients and how they resolve the conflicts. In-depth interviews were conducted with six Muslim counsellors at Public Institutions of Higher Education (PIHE) in Peninsular Malaysia using the grounded theory approach of Theoretical Sampling. The grounded theory process of data analysis was employed, starting with open coding, axial coding, and selective coding (Strauss & Corbin, 1990, 2008). The findings revealed that the Muslim counsellors wanted to achieve two therapeutic goals in counselling Muslim effeminate clients: giving insights and bringing about positive changes. To achieve those two goals, they go through four processes namely; building rapport, integrating religious values, facing conflicts and challenges and overcoming them. Muslim counsellors experienced conflicts as they counsell effeminate clients who are involved in activities prohibited by religion. The clients are involved in same-sex relationships, cross-dressing, prostitution, and some had intentions to undergo sex-change. To overcome these struggles, Muslim counsellors use three strategies, namely; seeking information, prioritising religious over professional values, and balancing between personal and professional interests. Based on the findings, this study made several recommendations for counsellor training institutions and professional associations, related government agencies, and accreditation bodies in Malaysia and elsewhere in the Muslim world.